Adaptive strategy of halophytic plants Polygonum maritimum and Euphorbia paralias - Kosakivska, I.V.; Babenko, L.M.; Shcherbatiuk, M.M.; Vedenicheva, N.P.; Sheyko, O.A.; Ivanova, A.; Angelova, L.; Maslenkova, L. (Reports of the National Academy of Sciences of Ukraine, 2017)
The leaf surface microstructure, pigments spectrum, phytohormones content, and lipids composition of halophytes with various metabolic and physiological strategies of adaptation to salinity of Polygonum maritimum L. and Euphorbia paralias L. grown under natural conditions on dunes of the Pomorie Lake (Bulgaria) are compared. P. maritimum stomata are located on the leaf both sides below the cuticle level, whereas, in E. raralias, stomata are present only on the abaxial side, and they are surrounded with hump-shaped cuticle constructions. A high amount of carotenoids (as compared with chlorophylls) in P. maritimum leaves indicates that these pigments have a light-collecting function and could transfer an additional energy to chlorophylls. In leaves of E. paralias and P. maritimum, free abscisic acid and conjugated indole-3-acetic acid prevailed. The inactive cytokinins (cis-zeatin and zeatin-O-glucoside) dominated in E. paralias leaves, whereas P. maritimum leaves contained a significant quantity of isopentenyl-type cytokinins. The presence of a large amount of saturated fatty acids provides a decrease of membrane permeability and better resistance against soil salinity. It is concluded that the ecological strategy of halophytes involves the complex of structural and functional adaptations and determines a successful existence under salinity conditions.